2022
DOI: 10.3390/antiox11101996
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant and Anti-Aging Effects of Phlorizin Are Mediated by DAF-16-Induced Stress Response and Autophagy in Caenorhabditis elegans

Abstract: Phlorizin (phloridzin) is a polyphenolic phytochemical primarily found in unripe Malus (apple). It is a glucoside of phloretin and acts as an inhibitor of renal glucose transport, thus lowering blood glucose. The objective of this study was to determine effects of dietary supplementation with phlorizin on stress response, aging, and age-related diseases using Caenorhabditis elegans as a model system. Survival after oxidative stress or ultraviolet irradiation was significantly increased by pre-treatment of phlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The IIS pathway, which regulates signal factors and activates a series of genes in the nucleus that mediate oxidative stress, is the most typical life-extending mechanism in C. elegans (Hesp et al 2015), with the daf-2, age-1, ak-1 and daf-16 genes playing a crucial role (Altintas et al 2016). The results suggested that phlorizin improved C. elegans survival by regulating daf-16 in the IIS pathway, and Suhyeon Park found similar results (Park and Park 2022). Mutations with decreased daf-2 activity have been found to more than double the longevity of animals (Zhang et al 2015), and the extension of lifespan is determined by the nuclear translocation of DAF-16 (Kitaoka et al 2016).…”
Section: Discussionmentioning
confidence: 75%
“…The IIS pathway, which regulates signal factors and activates a series of genes in the nucleus that mediate oxidative stress, is the most typical life-extending mechanism in C. elegans (Hesp et al 2015), with the daf-2, age-1, ak-1 and daf-16 genes playing a crucial role (Altintas et al 2016). The results suggested that phlorizin improved C. elegans survival by regulating daf-16 in the IIS pathway, and Suhyeon Park found similar results (Park and Park 2022). Mutations with decreased daf-2 activity have been found to more than double the longevity of animals (Zhang et al 2015), and the extension of lifespan is determined by the nuclear translocation of DAF-16 (Kitaoka et al 2016).…”
Section: Discussionmentioning
confidence: 75%
“…The treatment with DHA-TG specially enhanced the activity and expression of the SOD enzyme family. Since the effect of DHA-TG is lost in DAF-16 deficient strain, and the expression of sod-3 is very dependent on the factor DAF-16/FOXO [67], it might be hypothesized that healthspan-promoting effects of DHA-TG are closely related to the antioxidant response using DAF-16 as an intermediary, as stated in similar research [68,69].…”
Section: Discussionmentioning
confidence: 87%
“…Decreased hormone levels also significantly impact metabolism and cell death in post-trauma periods, which makes us hypothesize that restoring hormonal control of brain functions with exogenous hormones can serve as a pharmacological treatment to reduce the mortality of neurons and other brain cells, such as astrocytes and microglia. Although both compounds (phlorizin and phloretin) investigated here have demonstrated decisive anti-inflammatory actions [ 39 , 41 , 42 , 43 , 44 ], their possible molecular actions have not been studied in TBI. Our goal was to decipher which proteins regulated by phlorizin and phloretin, two natural compounds with estrogenic activity, can potentially regulate pro-oxidative and inflammatory mechanisms, which are the main hallmarks of TBI.…”
Section: Discussionmentioning
confidence: 99%